1999
DOI: 10.1021/es9900205
|View full text |Cite
|
Sign up to set email alerts
|

210Pb Atmospheric Flux and Growth Rates of a Microbial Mat from the Northwestern Mediterranean Sea (Ebro River Delta)

Abstract: Environmental archives are needed to study the variability of natural systems and the impact of man on them. Microbial mats, modern homologues of stromatolites, can be found in extreme environments such as the Ebro River Delta and were studied as potential environmental archives of atmospheric deposition. 210Pb, a radiotracer widely used in geochronology studies, was used both to determine the growth rates of a microbial mat from this environment and to estimate the 210Pb atmospheric flux in the northwestern M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…us, in the lower layer, distributions are clearly different for both radionuclides due to the different efficiency of the removal process of dissolved radionuclides by settling suspended particles. [84]. A more detailed evaluation may be seen in [85]; however the use of a mean value (which also is in good agreement with the average calculated by these last authors) is enough for our modelling purposes.…”
Section: 13supporting
confidence: 71%
“…us, in the lower layer, distributions are clearly different for both radionuclides due to the different efficiency of the removal process of dissolved radionuclides by settling suspended particles. [84]. A more detailed evaluation may be seen in [85]; however the use of a mean value (which also is in good agreement with the average calculated by these last authors) is enough for our modelling purposes.…”
Section: 13supporting
confidence: 71%
“…These are consistent with other values found in the scarce existing literature for the European continent from which 210 Pb xs inventory measured in peat bogs and estuarine sediments ranged between 2000 Bq m À2 and 9800 Bq m À2 and 210 Pb xs fluxes ranged between 60 Bq m À2 y À1 and 300 Bq m À2 y À1 (Carvalho, 1995;Cundy and Croudace, 1995b;Holynska et al, 1998;Gascó et al, 2006). Atmospheric 210 Pb xs fluxes have not been reported for the study area, although they have been established for other areas of the Iberian Peninsula, such as the West Mediterranean Sea where the flux is about 80 Bq m À2 y À1 (Sanchez-Cabeza et al, 1999), which is of the same order of that reported here.…”
Section: Pb Datingsupporting
confidence: 64%
“…We refer to these as “ecological” to represent intervals smaller than those of ontogenetic change, roughly equivalent to timescales of common biotic interactions. Modern microbial mats grow at variable rates, typically on the order of a few mm per year vertically (Buffan‐Dubau, Pringault, & de Wit, ; Sanchez‐Cabeza, Masqué, Martínez‐Alonso, Mir, & Esteve, ). Thus, footprints, commonly <0.5 mm in total relief, would have been obscured by mat regrowth over much shorter intervals.…”
Section: Implications For Dickinsoniamentioning
confidence: 99%